1991
DOI: 10.1021/jm00111a015
|View full text |Cite
|
Sign up to set email alerts
|

Octoclothepin enantiomers. A reinvestigation of their biochemical and pharmacological activity in relation to a new receptor-interaction model for dopamine D-2 receptor antagonists

Abstract: Octoclothepin (1) was resolved into its R and S enantiomers via the diastereomeric tartaric acid salts. The enantiomers were shown to be of high optical purity by 1H NMR with use of the chiral shift reagent (R)-(-)-2,2,2-trifluoro-1-(9-anthryl)ethanol. Pharmacological and biochemical testing confirmed that (S)-1 is the more potent dopamine (DA) D-2 antagonist both in vitro and in vivo, although the R enantiomer still has significant D-2 antagonistic activity. In contrast, both enantiomers were equally active i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…Recently, the model was further supported by a study of both enantiomers of octoclothepin. 11 The model has been used to rationalize the affinity for D2 receptors for compounds from different chemical classes such as dexclamol,10 butaclamol,12 benzamides,13 thioxanthenes,14 phenothiazines,14 cyproheptadine derivatives,15 and tetracyclic spiroamines. 15 Recently, it was shown that phenylindans, -indenes, and -indoles with high affinity for D2 receptors can also be well accommodated into the model.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the model was further supported by a study of both enantiomers of octoclothepin. 11 The model has been used to rationalize the affinity for D2 receptors for compounds from different chemical classes such as dexclamol,10 butaclamol,12 benzamides,13 thioxanthenes,14 phenothiazines,14 cyproheptadine derivatives,15 and tetracyclic spiroamines. 15 Recently, it was shown that phenylindans, -indenes, and -indoles with high affinity for D2 receptors can also be well accommodated into the model.…”
Section: Introductionmentioning
confidence: 99%
“…by inhibiting JAK kinases 20 . Octoclothepine inhibits GPCRs that elevate intracellular cAMP levels 21 , and cAMP impairs survival of BCR-Abl-expressing cells (see below).…”
Section: Resultsmentioning
confidence: 99%
“…An early study of ( S )‐ 14 (Fig. 7), neuroleptic compound that binds on dopamine D‐2 receptor [30], has revealed that stable conformation of ( S )‐ 14 , which is responsible for the dopamine D‐2 receptor antagonism, is significantly different from the one observed in the crystal [31].…”
Section: Resultsmentioning
confidence: 99%